The Glomerular Filtration Rate: From the Diagnosis of Kidney Function to a Public Health Tool - Cusumano, Ana Maria; Tzanno-Martins, Carmen; Rosa-Diez, Guillermo Javier (Frontiers in Medicine, 2021)
The prevalence of Chronic Kidney Disease (CKD) continues to increase worldwide, as well as the associated morbidity and mortality and the consequences on patients’ quality of life and countries’ economies. CKD often evolves without being recognized by patients and physicians, although the diagnosis is based on two simple laboratory data: the estimated Glomerular Filtration Rate (eGFR) and Urine Analysis. To measure GFR, the knowledge about the physiologic processes at the nephron level, the concept of clearance, and the identification of creatinine as a suitable endogenous marker for measuring creatinine clearance (CrCl) had to be previously developed. On those bases, different equations to calculate CrCl (Cockcroft & Gault, 1976), or estimated GFR (4 variables MDRD, 1999; CKD-Epi, 2009, among others) were generated. They all include creatinine and some demographic data, such as sex and age. But, to compare results throughout life or among laboratories, the creatinine determination must be standardized. In addition, the accuracy of these equations remains controversial in certain subgroups of patients. For these reasons, other mathematical models to improve CrCl estimation have been developed, such as when urine cannot be collected, in debilitated elderly patients and patients with trauma, diabetes, or obesity. Currently, eGFR in adults can be measured and reported immediately, using isotope dilution mass spectrometry traceable creatinine-based equations. In conclusion, based on knowledge obtained from renal physiology, eGFR can be used in the clinic for the diagnosis and early treatment of CKD, as well as a public instrument to estimate the prevalence.